Post-fire restoration of Mediterranean forests: Testing assembly rules mediated by facilitation - Siles, G; Rey, P J; Alcántara, J M (Basic and Applied Ecology, 2010)
In view of the importance of facilitative interactions between plants, nurse-based planting has been proposed as a restoration technique for Mediterranean vegetation. However, facilitation efﬁciency is known to depend on the environmental context and the particular pair of interacting species. Understanding these context- and pair-speciﬁc dependences is fundamental to understanding Mediterranean vegetation dynamics and to improving the use of nurse-based plantation for restoration. We assessed the effectiveness of nurse-based plantation and the signiﬁcance for post-ﬁre restoration of some assembly rules mediated by facilitation. In two nearby areas of different burning ages, we compared seedling establishment of 13 tall shrubs and trees planted in open ground and under nurses. Nurses and planted seedlings were selected from different life-forms. Tests of the assembly rules were provided by the partitioning of the statistical interaction effect between nurse and planted seedling life-forms in a two-factor design. Nurse-based plantation increased seedling survival 2–9 times compared to plantation in open ground, depending on the year. The higher efﬁciency of nurse-based plantation was consistent for the two burned areas and occurred in many species even in years with contrasting rainfall. We detected pair-speciﬁc differences in the efﬁciency of facilitation. This pair-speciﬁcity was partly explained by the dependence between life-forms of nurse and guest species, suggesting the existence of assembly rules. Our results conﬁrm that nurse-based plantation would be an appropriate post-ﬁre restoration technique in Mediterranean mountains under dry-subhumid climate, but suggest that attention to the life-form assemblage rules is needed for an efﬁcient implementation of such technique.
Keywords: Forest restoration; mediterranean fires; nurse effects; nurse plants; plant-plant interactions; post-fire regeneration; succession

Topography and forest composition affecting the variability in fire severity and post-fire regeneration occurring after a large fire in the Mediterranean basin - Broncano, M J; RETANA, J (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2004)
This study relates the spatial variability in tree regeneration generated by fire with topography and pre-fire vegetation composition, and analyses how the pattern of fire severities determines post-fire regeneration of the dominant tree species (Pinus halepensis and Quercus ilex) in a large fire that occurred in north-eastern Spain in summer 1994. At the fire level, the proportion of the different fire severities in the burned area was characteristic of large fires that burn with high severity. At the level of plot, the variability of fire severity in the study site depended on two topographic characteristics: elevation and aspect. Plots burned with high fire severity were distributed at higher altitude than less severely burned plots, which were mainly distributed in south- and east-facing slopes. Fire severity also increased with Q. ilex density in the stand. The mosaic of fire severities determined both plant mortality and seedling regeneration. Mortality of stems caused by fire was very high in both species, but many Q. ilex individuals resprouted after fire. Seedling regeneration of P. halepensis showed large differences among plots in the burned area, reflecting large spatial variability due to the elevation gradient, the variation in density of adult pine trees, and the spatial variability created by fire.
Keywords: mortality; post-fire regeneration; resprouting

Topography and forest composition affecting the variability in fire severity and post-fire regeneration occurring after a large fire in the Mediterranean basin - Broncano, M. J.; Retana, J. (INTERNATIONAL JOURNAL OF WILDLAND FIRE, 2004)
This study relates the spatial variability in tree regeneration generated by fire with topography and pre-fire vegetation composition, and analyses how the pattern of fire severities determines post-fire regeneration of the dominant tree species (Pinus halepensis and Quercus ilex) in a large fire that occurred in north-eastern Spain in summer 1994. At the fire level, the proportion of the different fire severities in the burned area was characteristic of large fires that burn with high severity. At the level of plot, the variability of fire severity in the study site depended on two topographic characteristics: elevation and aspect. Plots burned with high fire severity were distributed at higher altitude than less severely burned plots, which were mainly distributed in south- and east-facing slopes. Fire severity also increased with Q. ilex density in the stand. The mosaic of fire severities determined both plant mortality and seedling regeneration. Mortality of stems caused by fire was very high in both species, but many Q. ilex individuals resprouted after fire. Seedling regeneration of P. halepensis showed large differences among plots in the burned area, reflecting large spatial variability due to the elevation gradient, the variation in density of adult pine trees, and the spatial variability created by fire.
The following values have no corresponding Zotero field: pub-location: 150 OXFORD ST, PO BOX 1139, COLLINGWOOD, VICTORIA 3066, AUSTRALIA publisher: C S I R O PUBLISHING
Keywords: mortality; post-fire regeneration; resprouting